N-myc downstream regulated gene 1 (ndrg1) functions as a molecular switch for cellular adaptation to hypoxia - Park, Jong S; Gabel, Austin M; Kassir, Polina; Kang, Lois; Chowdhary, Prableen K; Osei-Ntansah, Afia; Tran, Neil D; Viswanathan, Soujanya; Canales, Bryanna; Ding, Pengfei; Lee, Young-Sam; Brewster, Rachel (eLife, 2022)
Lack of oxygen (hypoxia and anoxia) is detrimental to cell function and survival and underlies many disease conditions. Hence, metazoans have evolved mechanisms to adapt to low oxygen. One such mechanism, metabolic suppression, decreases the cellular demand for oxygen by downregulating ATP-demanding processes. However, the molecular mechanisms underlying this adaptation are poorly understood. Here, we report on the role of ndrg1a in hypoxia adaptation of the anoxia-tolerant zebrafish embryo. ndrg1a is expressed in the kidney and ionocytes, cell types that use large amounts of ATP to maintain ion homeostasis. ndrg1a mutants are viable and develop normally when raised under normal oxygen. However, their survival and kidney function is reduced relative to WT embryos following exposure to prolonged anoxia. We further demonstrate that Ndrg1a binds to the energy-demanding sodium-potassium ATPase (NKA) pump under anoxia and is required for its degradation, which may preserve ATP in the kidney and ionocytes and contribute to energy homeostasis. Lastly, we show that sodium azide treatment, which increases lactate levels under normoxia, is sufficient to trigger NKA degradation in an Ndrg1a-dependent manner. These findings support a model whereby Ndrg1a is essential for hypoxia adaptation and functions downstream of lactate signaling to induce NKA degradation, a process known to conserve cellular energy.
Keywords: NDRG1; hypoxia; anoxia; hypometabolism; lactate; sodium-potassium pump